2015
DOI: 10.1016/j.ejbt.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aroma quality on the biotransformation of natural 2-phenylethanol produced using ascorbic acid

Abstract: butyric acid > isobutyric acid > butanol. The sample that exhibited the best similarity to the standard 2-PE sample (99.19%) was the sample to which ascorbic acid had been added during glucose metabolism. Conclusions 2-PE produced through the addition of ascorbic acid exhibited the closest aroma similarity to the standard 2-PE sample.]]>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
0
11
0
3
Order By: Relevance
“…In our previous study, the medium condition suitable for our other engineering strains for 2-PE synthesis was established [ 10 , 18 ]. In preliminary experiments of this study, the affection of NaCl on 2-PE synthesis was tested, differently, our results showed that NaCl suppressed 2-PE synthesis in our module strain, not necessary as for strain reported by Tian et al [ 48 ], which might be owing to strains’ differences. The results of affection of inorganic salts on 2-PE synthesis in our study showed that the engineering strain YS58(G1-A8-A10-A2)-GDH produced higher 2-PE when 5 g L −1 MgSO 4 ·7H 2 O and 5 g L −1 KH 2 PO 4 were contained in the medium (Fig.…”
Section: Resultsmentioning
confidence: 43%
“…In our previous study, the medium condition suitable for our other engineering strains for 2-PE synthesis was established [ 10 , 18 ]. In preliminary experiments of this study, the affection of NaCl on 2-PE synthesis was tested, differently, our results showed that NaCl suppressed 2-PE synthesis in our module strain, not necessary as for strain reported by Tian et al [ 48 ], which might be owing to strains’ differences. The results of affection of inorganic salts on 2-PE synthesis in our study showed that the engineering strain YS58(G1-A8-A10-A2)-GDH produced higher 2-PE when 5 g L −1 MgSO 4 ·7H 2 O and 5 g L −1 KH 2 PO 4 were contained in the medium (Fig.…”
Section: Resultsmentioning
confidence: 43%
“…For instance, 2‐phenylethanol (2‐PE) is an aroma compound with a rose‐like odors, which is widely used in perfume, cosmetics, and food industries . Its market size is expected to reach $700 million by 2019 with its annual global demand of >10,000 tons . Friedel‐craft reaction and catalytic reduction of styrene oxide are the two chemical methods used for industrial production of this chemical.…”
Section: Introductionmentioning
confidence: 99%
“…With the supply of L‐ Phe, maximum 2‐PE concentration of ∼3.8 g/L was achieved, together with other byproducts. The generation of a mixture affects the yield and aroma quality of 2‐PE and makes the downstream process costly and difficult . Moreover, the biotransformation with yeast growing cells gave low production rate and suffered from product inhibition .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations